Effect of potassium on ventilation in the rhesus monkey. - Paterson, D; Dorrington, K; Bergel, D; Kerr, G; Miall, R; Stein, J; Nye, P (1992)
Increasing the concentration of arterial plasma K+ to 6-8 mM increased ventilation in two sedated analgesic-treated rhesus monkeys who had their end-tidal CO2 held constant during euoxia (arterial oxygen pressure, Pa,O2, ca 100 Torr) and hypoxia (Pa,O2, ca 40 Torr). During euoxia and hypoxia, hyperkalaemia increased ventilation up to 40 and 250%, respectively. This effect was reduced in euoxia and virtually abolished in hypoxia following an abrupt switch to 100% oxygen. Thus the ventilatory response of this primate to hyperkalaemia is at least as sensitive as that of the cat and if hypoxia is added the two stimuli generate a powerful drive to breathing.